New therapeutic perspectives to manage refractory immune checkpoint-related toxicities. Issue 1 (January 2019) - Martins, Filipe; Sykiotis, Gerasimos P; Maillard, Michel; Fraga, Montserrat; Ribi, Camillo; Kuntzer, Thierry; Michielin, Olivier; Peters, Solange; Coukos, Georges; Spertini, Francois; Thompson, John A; Obeid, Michel
Summary: Immune checkpoint inhibitors are reshaping the prognosis of many cancer and are progressively becoming the standard of care in the treatment of many tumour types. Immunotherapy is bringing new hope to patients, but also a whole new spectrum of toxicities for healthcare practitioners to manage. Oncologists and specialists involved in the pluridisciplinary management of patients with cancer are increasingly confronted with the therapeutic challenge of treating patients with severe and refractory immune-related adverse events. In this Personal View, we summarise the therapeutic strategies that have been used to manage such toxicities resulting from immune checkpoint inhibitor treatment. On the basis of current knowledge about their pathogenesis, we discuss the use of new biological and non-biological immunosuppressive drugs to treat severe and steroid refractory immune-related adverse events. Depending on the immune infiltrate type that is predominant, we propose a treatment algorithm for personalised management that goes beyond typical corticosteroid use. We propose a so-called shut-off strategy that aims at inhibiting key inflammatory components involved in the pathophysiological processes of immune-related adverse events, and limits potential adverse effects of drug immunosuppression on tumour response. This approach develops on current guidelines and challenges the step-by-step increase approach to drug immunosuppression.